ANALISIS DAYA DUKUNG LAHAN BERBASIS SISTEM INFORMASI GEOGRAFIS DI KAWASAN PERMUKIMAN DUSUN GUNUNG MALATI, KABUPATEN CIANJUR - Alifhia Rizqy Nabilah; Veronika Widi Prabawasari; Dewi Astuti (Asosiasi Dosen Muda Indonesia, 2023)
The residential area of ​​Gunung Malati, Karyamukti Village, Campaka District, Cianjur Regency is a village in a hilly environment with an elevation of 900 - 1000 m above sea level and a slope approaching the steep category of 8o -25o. With this geographical condition, the people of Gunung Malati Village, where almost 80% work as UMKM players, are located on land that has a high vulnerability to the risk of natural disasters. This study aims to analyze land capability in settlements, as well as to find out how many residential houses the residents built on land that was not suitable for settlements. The research method used is a quantitative method where there is primary data collection, and a spatial analysis approach using a Geographic Information System (GIS). The research results obtained are that most of the residential areas of Gunung Malati Village are in the classification of low land development capability with a maximum land cover recommendation of 10%, there are even no guidelines for built-up land (non-building) because it is located in an area with a relatively high potential for natural disasters. at risk in 47 residential buildings. The results of this study are useful as a determinant of the suitability of land use in Gunung Malati Village, to reduce the high level of risk in the Gunung Malati Village when natural disasters occur.